Involvement of Differential Relationship between HCV Replication and Hepatic PRR Signaling Gene Expression in Responsiveness to IFN-Based Therapy. (29th December 2013) - Yuki, Nobukazu; Matsumoto, Shinji; Kato, Michio; Yamaguchi, Toshikazu
Abstract : Aim . To gain an insight into the effect of HCV replication-associated interference with the IFN system on hepatic mRNA expression involved in IFN production. Methods . Relative mRNA expression of TLR3/RIG-I signaling genes involved in IFN- β production was correlated with positive- and negative-strand HCV RNAs in pretreatment liver tissues responsive and nonresponsive to peginterferon and ribavirin for chronic hepatitis C genotype 1. Treatment response was analyzed for per protocol population at weeks 12 (n = 45 ) and 24 (n = 40 ) and at 24 weeks aftertreatment (n = 38 ). Results . HCV replication had no relation to the expression of TLR3, RIG-I, TRIF, IPS-1, IRF3, and IFN- β mRNAs in responders. In striking contrast, positive- and/or negative-strand HCV showed positive correlations with TLR3, RIG-I, TRIF, IPS-1, and IRF3 mRNAs in week-12 nonresponders; with RIG-I, TRIF, IPS-1, and IRF3 mRNAs in week-24 nonresponders; and with TLR3, RIG-I, and IRF3 mRNAs in posttreatment nonresponders. Thus mRNA expression of TLR3/RIG-I signaling genes was increased in relation to viral replication in nonresponders. Conclusions . The findings in IFN nonresponders may imply a host feedback response to severe impairment of the IFN system associated with HCV replication.